In Vitro and In Vivo Investigation of the Angiogenic Effects of Liraglutide during Islet Transplantation. - Allan Langlois; Carole Mura; William Bietiger; Elodie Seyfritz; Camille Dollinger; Claude Peronet; Elisa Maillard; Michel Pinget; Nathalie Jeandidier; Séverine Sigrist (PLoS ONE)
Introduction This study investigated the angiogenic properties of liraglutide in vitro and in vivo and the mechanisms involved, with a focus on Hypoxia Inducible Factor-1α (HIF-1α) and mammalian target of rapamycin (mTOR). Materials and methods Rat pancreatic islets were incubated in vitro with 10 μmol/L of liraglutide (Lira) for 12, 24 and 48 h. Islet viability was studied by fluorescein diacetate/propidium iodide staining and their function was assessed by glucose stimulation. The angiogenic effect of liraglutide was determined in vitro by the measure of vascular endothelial growth factor (VEGF) secretion using enzyme-linked immunosorbent assay and by the evaluation of VEGF and platelet-derived growth factor-α (PDGFα) expression with quantitative polymerase chain reaction technic. Then, in vitro and in vivo, angiogenic property of Lira was evaluated using immunofluorescence staining targeting the cluster of differentiation 31 (CD31). To understand angiogenic mechanisms involved by Lira, HIF-1α and mTOR activation were studied using western blotting. In vivo, islets (1000/kg body-weight) were transplanted into diabetic (streptozotocin) Lewis rats. Metabolic control was assessed for 1 month by measuring body-weight gain and fasting blood glucose. Results Islet viability and function were respectively preserved and enhanced (p<0.05) with Lira, versus control. Lira increased CD31-positive cells, expression of VEGF and PDGFα (p<0.05) after 24 h in culture. Increased VEGF secretion versus control was also observed at 48 h (p<0.05). Moreover, Lira activated mTOR (p<0.05) signalling pathway. In vivo, Lira improved vascular density (p<0.01), body-weight gain (p<0.01) and reduced fasting blood glucose in transplanted rats (p<0.001). Conclusion The beneficial effects of liraglutide on islets appeared to be linked to its angiogenic properties. These findings indicated that glucagon-like peptide-1 analogues could be used to improve transplanted islet revascularisation.